Microneedle patches at the bio-agricultural Interface: Toward precision, resilience, and sustainability - Fangzheng Zhou; Xiaochen Huang; Yaqi Teng; Ping Yu; Boqiang Li; Haowen Sun; Yixin Gao; Ruikun He; Wei Sun; Bei Fan; Xiaoxue Jia; Long Li; et al. (Food Research International, 2026)

Corrigendum to “Rgn couples proliferative EGFR-JAK/STAT signaling and the notch/insulin differentiation-metabolism axis during epithelial repair in Drosophila” [Insect Biochem. Mol. Biol. 2026 191 104549] - Ping Wang; Xianhao Li; Xinyan Teng; Bing Bi; Li Hua Jin (Insect Biochemistry and Molecular Biology, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Self-assembled carrier-free Cur@EGCG-Cu rescue inflammatory senescence and restore autophagy in tendinopathy - Yu Zhang; Qiqi Lou; Ran Yang; Xiang Li; Xiangkai Kong; Ruolin Cui; Ni Ni; Lilun Jin; Weiran Teng; Ping Gu (Chemical Engineering Journal, 2026)

ERBB2 as a Prognostic Biomarker in Prostate Cancer: Integration of Single-Cell Transcriptomics, Deep Learning, and Immunohistochemical Validation - Chen Wang; Li-Jing Zhu; Wei-Bo Mao; Ting Chen; Teng-Fei Gu; Sheng-Ping Hu; Yong-Tao Pan; Guo-Lin Yan; Yun-Peng Dong; Jie Li (Biochemical Genetics, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Biochar derived from shell waste: Adsorption of phosphorus from aqueous solutions and potential application as slow-release fertilizer - Shanshan Zhu; Yuting Lu; Tao Li; Yine Li; Pengfei Liu; Jiangfeng Teng; Chao Huang; Yuxin Jiang; Ping Wang (Journal of Environmental Chemical Engineering, 2026)

Rgn couples proliferative EGFR-JAK/STAT signaling and the notch/insulin differentiation-metabolism axis during epithelial repair in Drosophila - Ping Wang; Xianhao Li; Xinyan Teng; Bing Bi; Li Hua Jin (Insect Biochemistry and Molecular Biology, 2026)

Sedative effects and stress-alleviating capabilities of four dietary plant-derived compounds on Procambarus clarkii - Zihao Li; Xinyi Xie; Ziqian Sun; Zhaoxuan Zhu; Shuang Zhang; Xiaoyan Liang; Mengyu Teng; Haitang Wang; Xiuhong Liu; Ping Yang; Xingxing Fang (Veterinary Research Communications, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Chemical constituents from Helvella leucopus and their chemotaxonomic significance - Zhao-Zhao Zhang; Yi-Yang Xie; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2026)

Fe2O3@diatomite heterogeneous fenton system for enhancing phosphorus bioavailability in dredged sediment - Wenmin Li; Jian Zhu; Pei Wu; Hongchun Huang; Xindeng Huang; Mengyan Wu; Ying Zhang; Kangrong Xiang; Jiangfeng Teng; Chang Sun; Ao Tan; Mingjing Lei; et al. (Journal of Environmental Chemical Engineering, 2025)

Shape memory hydrogel for preventing coal spontaneous combustion: Properties and engineering applications - Di Xue; Zhen Qiu; Siyu Teng; Wei Lu; Yizhuo Wang; Jinliang Li; Jinhu Li; Ping Chang (Process Safety and Environmental Protection, 2025)

[3 + 2 + 1] iridium(III) complexes for high-efficiency saturated red organic light-emitting diodes - Ping Chen; Qingwu Wu; Gui-Yan Yang; Qifei Xie; Sheng Yu; Ming-Yu Teng; Huabo Han; Guo-Li Huang; You-Xuan Zheng; Guangzhao Lu (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Polycyclic polyprenylated acylphloroglucinols with cytotoxicity against human tongue squamous carcinoma cells in vitro from Hypericum curvisepalum - Min-Min Cao; Xian Wei; Jie Huang; Zhong-Qiu Gan; Li-Ping Teng; Zhong-Bo Zhou (Phytochemistry Letters, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Conventional and biodegradable microplastics affected arsenic mobility and methylation in paddy soils through distinct chemical-microbial pathways - Hai-Qian Li; Jin-Peng Lv; Yue-Hui Jia; Jie Liu; Qiong Liang; Jian Zhou; Ai-Zhen Yang; Teng Yan; Yu-Ping Yang; Gui-Lan Duan (Journal of Hazardous Materials, 2025)

Analysis of carbon reduction potential from typical municipal solid waste incineration plants under MSW classification - Chenqi Gao; Rongxing Bian; Ping Li; Chengyue Yin; Xiao Teng; Jinran Zhang; Shudan Gao; Yating Niu; Yingjie Sun; Yanan Wang; Huawei Wang (Journal of Environmental Management, 2025)

Chemical constitutents and chemotaxonomic research of the deep-sea-derived fungus Talaromyces minioluteus W19 - Kai Zhang; Yuan Wang; Teng Long; Ya-Ping Xie; Zheng-Biao Zou; Yong Zhang; You Li; Ming-Min Xie; Guang-Ming Liu; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

Organic carbon preservation in wetlands: Iron oxide protection vs. thermodynamic limitation - Fu-Sheng Sun; Chao Ma; Guang-Hui Yu; Yakov Kuzyakov; Yun-Chao Lang; Ping-Qing Fu; Li-Jun Guo; Hui Henry Teng; Cong-Qiang Liu (Water Research, 2023)

The intramolecular integration of carbonyl and N-nitroamino groups to effectively balance the energy and sensitivity of N-nitroamino-functionalized bisazoles - Jinxiong Cai; Jinya Zhang; Jin Xiong; Rui Li; Teng Fei; Qi Lai; Ping Yin; Siping Pang (Chemical Engineering Journal, 2023)

miR-155 Regulates Photoperiod Induced Gonadal Development in Atlantic Salmon (Salmo salar) by Targeting Brain-Derived Neurotrophic Factor - Teng Guo; Yanfeng Wang; Ping Jiang; Jun Li; Qinghua Liu; Liang Chi (Fishes, 2023)
This study was designed to explore the impact of the photoperiod on the gonadal development and somatic growth of Atlantic salmon raised in recirculating aquaculture systems (RASs), with specific focus on the role that microRNA (miR)-155 plays as a regulator in the Atlantic salmon’s photoperiodic reproduction. These salmon were reared for 5 months under six different photoperiod regimens, including two with changing photoperiods (LL–SL = 24L:0D–8L:16D and SL–LL = 8L:16D–24L:0D) and four with constant photoperiods (24L:0D, 18L:6D, 12L:12D, and 8L:16D). The longer photoperiod groups (LL–SL and 24L:0D) were ultimately associated with higher gonadosomatic index (GSI) values and an increased proportion of mature fish relative to other exposure groups, indicating that the photoperiod positively impacted the Atlantic salmon’s gonadal development in RAS environments. Hypothalamic miR-155 expression in these Atlantic salmon was also found to be influenced by the photoperiod, showing a markedly decreased expression in salmon exposed to a long photoperiod and upregulation following rearing under a short photoperiod. Functionally, miR-155 was found to suppress the expression of gonadal axis-related genes, including FSH and GnRH, through its ability to target the brain-derived neurotrophic factor (BDNF) and to thereby regulate photoperiod reproduction. Overall, these results suggested that the photoperiod could regulate gonad development in Atlantic salmon with miRNA-155 being involved in this process by targeting the BDNF.

SOV sensitizes gastric cancer cells to radiation by suppressing radiation-induced autophagy in vitro and in vivo - Wen Wang; Xiao-gan Jiang; Ya-ping Bai; Heng Li; Ling-xi Gao; Teng Zhang; Fang-yi Dong; Wen-ping Ding; Yan Zhang (Tissue and Cell, 2023)

PSS modified by 3-aminopropyltrimethoxysilane linking large-area GNPs/PSS to silicone rubber with stable interface combination for high sensitivity flexible resistive sensor - Han Feng; Ping Liu; Xu Guo; Junliang Li; Yifan Sun; Shunge Wu; Ruohai Hu; Zhi Liu; Helei Tian; Yuanming Ma; Caixia Liu; Houzhu Huang; et al. (Chemical Engineering Journal, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Genome-wide transcriptome analysis uncovers gene networks regulating fruit quality and volatile compounds in mango cultivar 'Tainong' during postharvest - Li Li; Ping Yi; Jian Sun; Jie Tang; Guoming Liu; Jinfeng Bi; Jianwen Teng; Meijiao Hu; Fang Yuan; Xuemei He; Jinfeng Sheng; Ming Xin; et al. (Food Research International, 2023)

Abnormal fatty acid metabolism and ceramide expression may discriminate myocardial infarction from strangulation death: A pilot study - Song-Jun Wang; Bing-Rui Liu; Fu Zhang; Ya-Ping Li; Xiao-Rui Su; Chen-Teng Yang; Bin Cong; Zhi-Hua Zhang (Tissue and Cell, 2023)

Smog chamber study of secondary organic aerosol formation from gas- and particle-phase naphthalene ozonolysis - Jixing Liu; Shuping Zhu; Teng Guo; Bin Jia; Li Xu; Jun Chen; Ping Cheng (Atmospheric Environment, 2023)

Streptomyces: Derived Active Extract Inhibits Candida albicans Biofilm Formation - Sheng-qiang Yang; Hui-jie Zhou; Li-ping Teng; Hong Zeng (Current Microbiology, 2022)

Early Carboniferous high-silica granites in the Kalejun Mountains, Chinese western Tianshan: Petrogenesis, tectonic setting and geodynamic implications for the South Tianshan Ocean - Yaoqing Luo; Yongjun Li; Zuopeng Wang; Gaoxue Yang; Ping Shen; Mingyao Teng; Weining Wang; Haoying Chang (International Geology Review, 2022)

Scalp Acupuncture Protects Against Neuronal Ferroptosis by Activating The p62-Keap1-Nrf2 Pathway in Rat Models of Intracranial Haemorrhage - Ming-Yue Li; Xiao-Hong Dai; Xue-Ping Yu; Wei Zou; Wei Teng; Peng Liu; Xin-Yang Yu; Qi An; Xin Wen (Journal of Molecular Neuroscience, 2022)
Intracerebral haemorrhage (ICH) can be a catastrophic event; even if the initial stages of the pathology were well-managed, a number of patients experience varied residual neurological deficits following the insult. Ferroptosis is a recently identified type of cell demise which is tightly linked to the neurological impairment associated with ICH. In the current work, the prophylactic impact of scalp acupuncture (SA) therapy on autologous blood injection murine models of ICH was investigated in order to establish whether SA could mitigate the secondary damage arising following ICH by moderating ferroptosis. The pathophysiological mechanisms associated with this process were also explored. Ludmila Belayev tests were utilised for the characterisation of neurological damage. Haematoxylin–eosin staining was employed in order to determine the cerebral impact of the induced ICH. Malondialdehyde (MDA) and iron titres in peri-haemorrhagic cerebral tissues were appraised using purchased assay kits. Transmission electron microscopy delineated mitochondrial appearances within nerve cell bodies from the area of haemorrhage. Western blotting techniques were utilised to assay the degree of protein expression of NeuN, sequestosome 1 (p62), nuclear factor erythroid 2-related factor 2 (Nrf2), Kelch-like ECH-associated protein 1 (Keap1), glutathione peroxidase 4 (GPX4) and ferritin heavy chain 1 (FTH1). The frequencies of Nrf2, GPX4 and FTH1 positive cells, respectively, were documented with immunohistochemical staining. The results demonstrated that therapy with SA after ICH mitigated MDA and iron sequestration, diminished the appearance of contracted mitochondria with increased outer mitochondrial membrane diameter within the nerve cell bodies, and suppressed neuronal ferroptosis. The pathways responsible for these effects may encompass amplified p62, Nrf2, GPX4 and FTH1 expression, together with decreased Keap1 expression. Application of SA reduced identified neurobehavioural abnormalities after ICH; no disparities were observed between the consequences of SA therapy and deferoxamine delivery. It can be surmised that intervention with SA enhanced recovery after ICH by triggering the antioxidant pathway, p62/Keap1/Nrf2, and causing FTH1 and GPX4 upregulation, factors that participate in diminishing excess iron and thus in mitigating lipid peroxidation insults arising from ferroptosis following ICH.

C-dot doping for enhanced catalytic performance of TiO2/5A for toluene degradation in non-thermal plasma-catalyst system - Jixing Liu; Yanyan Ji; Shuping Zhu; Teng Guo; Li Xu; Junguo Dong; Ping Cheng (Environmental Science and Pollution Research, 2022)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Sucrose fatty acid esters: synthesis, emulsifying capacities, biological activities and structure-property profiles - Yinglai Teng; Scott G. Stewart; Yao-Wen Hai; Xuan Li; Martin G. Banwell; Ping Lan (Critical Reviews in Food Science and Nutrition, 2021)

Tracking fluid sources for skarn formation using scapolite geochemistry: an example from the Jinshandian iron skarn deposit, Eastern China - Li-Ping Zeng; Xin-Fu Zhao; Johannes Hammerli; Tian-Wei-Teng Fan; Carl Spandler (Mineralium Deposita, 2020)

Real-time monitoring and quantification of organic by-products and mechanism study of acetone decomposition in a dielectric barrier discharge reactor - Xueshuang Li; Teng Guo; Zhen Peng; Li Xu; Junguo Dong; Ping Cheng; Zhen Zhou (Environmental Science and Pollution Research, 2019)

Molecular characterization of two novel sub-sublineages of pigeon paramyxovirus type 1 in China - Tianchao Wei; Qiaomu Deng; Haiqiong Li; Chao Pan; Guosheng Zhai; Yadong Yuan; Ercai Cheng; Yuanqin Zhang; Meilan Mo; Teng Huang; Ping Wei (Archives of Virology, 2018)

Lappaconitine, a C18-diterpenoid alkaloid, exhibits antihypersensitivity in chronic pain through stimulation of spinal dynorphin A expression - Ming-Li Sun; Jun-Ping Ao; Yi-Rui Wang; Qian Huang; Teng-Fei Li; Xin-Yan Li; Yong-Xiang Wang (Psychopharmacology, 2018)

The Role of HINT1 in Methamphetamine-Induced Conditioned Place Preference - Ju-ping Li; Peng Liu; Gang Lei; Zheng Chu; Fei Liu; Chao-feng Shi; Yong-hui Dang; Teng Chen (Neurotoxicity Research, 2018)

Diversity and evolution analysis of glycoprotein GP85 from avian leukosis virus subgroup J isolates from chickens of different genetic backgrounds during 1989-2016: Coexistence of five extremely different clusters - Peikun Wang; Lulu Lin; Haijuan Li; Yongli Yang; Teng Huang; Ping Wei (Archives of Virology, 2018)

Full-length genome sequence analysis of four subgroup J avian leukosis virus strains isolated from chickens with clinical hemangioma - Lulu Lin; Peikun Wang; Yongli Yang; Haijuan Li; Teng Huang; Ping Wei (Virus Genes, 2017)

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications - Wang-Ye Li; Fang-Zhen Teng; Yilin Xiao; Hai-Ou Gu; Xiang-Ping Zha; Jian Huang (Contributions to Mineralogy and Petrology, 2016)

The Oldest Cranium of Sinomastodon (Proboscidea, Gomphotheriidae), Discovered in the Uppermost Miocene of Southwestern China: Implications for the Origin and Migration of This Taxon - Shi-Qi Wang; Xue-Ping Ji; Nina G. Jablonski; Denise F. Su; Jun-Yi Ge; Chang-Fen Ding; Teng-Song Yu; Wen-Qi Li; Jaroon Duangkrayom (Journal of Mammalian Evolution, 2016)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

Blood–brain barrier permeability change and regulation mechanism after subarachnoid hemorrhage - Zhiqing Li; Guobiao Liang; Teng Ma; Jingchen Li; Ping Wang; Libo Liu; Bo Yu; Yunhui Liu; Yixue Xue (Metabolic Brain Disease, 2015)

In vivo expression patterns of microRNAs of Gallid herpesvirus 2 (GaHV-2) during the virus life cycle and development of Marek’s disease lymphomas - Pu Zhao; Xiu-Jie Li; Man Teng; Lu Dang; Zu-Hua Yu; Jia-Qi Chi; Jing-Wei Su; Gai-Ping Zhang; Jun Luo (Virus Genes, 2015)

The host HLA-A*02 allele is associated with the response to pegylated interferon and ribavirin in patients with chronic hepatitis C virus infection - Meng Wang; Jian-sheng Li; Yu Ping; Zhi-qin Li; Li-ping Wang; Qian Guo; Zhen Zhang; Dong-li Yue; Fei Wang; Teng-fei Zhang; Mohammad Serajul Islam; Yi Zhang (Archives of Virology, 2015)

Variable-coordinate forward modeling of irregular surface based on dual-variable grid - Jian-Ping Huang; Ying-Ming Qu; Qing-Yang Li; Zhen-Chun Li; Guo-Lei Li; Chang-Cheng Bu; Hou-Hua Teng (Applied Geophysics, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Genetic Diversity and Population Structure of Seedling Populations of Pyrus pashia - Yu Zong; Ping Sun; Jing Liu; Xiaoyan Yue; Kunming Li; Yuanwen Teng (Plant Molecular Biology Reporter, 2014)

Exposure to diethylhexyl phthalate (DEHP) results in a heritable modification of imprint genes DNA methylation in mouse oocytes - Lan Li; Teng Zhang; Xun-Si Qin; Wei Ge; Hua-Gang Ma; Li-Lan Sun; Zhu-Mei Hou; Hong Chen; Ping Chen; Guo-Qing Qin; Wei Shen; Xi-Feng Zhang (Molecular Biology Reports, 2014)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Genetic structure and phylogeography of Pyrus pashia L. (Rosaceae) in Yunnan Province, China, revealed by chloroplast DNA analyses - Jing Liu; Ping Sun; Xiaoyan Zheng; Daniel Potter; Kunming Li; Chunyun Hu; Yuanwen Teng (Tree Genetics & Genomes, 2013)

Crystal structure and activating effect on RyRs of AhV_TL-I, a glycosylated thrombin-like enzyme from Agkistrodon halys snake venom - Fuxing Zeng; Bing Shen; Zhongliang Zhu; Ping Zhang; Yonghua Ji; Liwen Niu; Xu Li; Maikun Teng (Archives of Toxicology, 2013)

Widespread expression of zinc transporter ZnT (SLC30) family members in mouse endocrine cells - Man-Li Zhong; Zhi-Hong Chi; Zhong-Yan Shan; Wei-Ping Teng; Zhan-You Wang (Histochemistry and Cell Biology, 2012)

Molecular biomarkers of colorectal cancer: prognostic and predictive tools for clinical practice - Wei-qin Jiang; Fang-fang Fu; Yang-xia Li; Wei-bin Wang; Hao-hao Wang; Hai-ping Jiang; Li-song Teng (Journal of Zhejiang University-SCIENCE B, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Molecular epidemiological investigation of Marek’s disease virus from Guangxi, China - Li-qiong Teng; Ping Wei; Zhong-bao Song; Jun-jun He; Zhi-zhong Cui (Archives of Virology, 2011)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Effects of soil amendment with different carbon sources and other factors on the bioremediation of an aged PAH-contaminated soil - Ying Teng; Yongming Luo; Lifeng Ping; Dexun Zou; Zhengao Li; Peter Christie (Biodegradation, 2010)

Effects of cefotaxime and kanamycin on thallus proliferation and differentiation in Porphyra yezoensis and their inhibition on Agrobacterium tumefaciens - Ping Wang; Gang Wang; Yajuan Teng; Xinshu Li; Jing Ji; Xinghong Xu; Yongzhong Li (Marine Biology Research, 2010)

Effect of CO2 enrichment on the glucosinolate contents under different nitrogen levels in bolting stem of Chinese kale (Brassica alboglabra L.) - Gui-xiao La; Ping Fang; Yi-bo Teng; Ya-juan Li; Xian-yong Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Molecular characterization of germline mutations in the BRCA1 and BRCA2 genes from breast cancer families in Taiwan - Steven Shoei-Lung Li; H.-M. Tseng; Tsui-Ping Yang; Chia-Han Liu; Shiuh-Jen Teng; Hung-Wen Huang; L.-M. Chen; Hsiao-Wei Kao; Jimmy H. Chen; Jau-Neng Tseng; Angela Chen; Ming-Feng Hou; et al. (Human Genetics, 1999)